(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2006)
A small pachypleurosaurid collected in the Besano area of Italy, is described. A comparative analysis of size and proportions with other pachipleurosaurids suggest it represents a juvenile specimen of Neusticosaurus pusillus. The specimen represents a peculiar taphonomic case: the centra of the dorsal vertebrae are clustered together in the pectoral area while the rest of the trunk is virtually undisturbed, suggesting that disarticulation of dorsal vertebral elements may have occurred before decay of integumental soft parts, possibly before the carcass reached the bottom of the basin.